Evolução espaço-temporal da Síndrome de Imunodeficiência Adquirida - AIDS na faixa de fronteira do Paraná - Bauermann, César Luis (2017)
This dissertation aims to analyze the space-time evolution of the Acquired Immunodeficiency Syndrome - AIDS in the 139 municipalities belonging to the Border Range of the state of Paraná in the period that covers the years 1985 to 2010. The data collection was performed with the Departamento de informação e informática - DATASUS a body of the Ministry of Health that centralizes and makes available the data of the main national health and Sistema de Informação de Agravos de Notificação - SINAN Public Health Information System that publicly makes available the annual data of AIDS notifications in the national territory. The variables studied were: gender, age, schooling, notification year and municipality of residence. Between 1985 and 2010, there were 4,270 AIDS cases in the border region of Paraná, with a predominance of males with a higher proportion of cases (55.3%) (2,365). Spatio-temporal analysis has shown that the disease has been spreading from the largest urban centers to medium and small municipalities where the availability and monitoring of preventive interventions and treatment are relevant challenges. The presence of the international political boundary shows unique dynamics as the epidemic progresses, due to population mobility and poor control policies, especially in the so-called twin cities. The transmission of this disease is directly linked to human mobility in the geographic space, which contributes to the diffusion of the etiological agent. The municipalities of Cascavel and Foz do Iguaçu concentrate the largest number of notifications, evidencing their representativeness within the study clipping. It is also highlighted the influence of these in surrounding municipalities and the tendency of an internalization of the pathology in the Border Range of Paraná.